HIV/AIDS and the Responsibility for the “Other” in African Community (Hekima Review, 2006)
People of the Sub-Saharan African Countries have faced many calamities in their historical development, brought about by slavery, colonization, dictatorship, diseases etc. African people are not the only victims of disasters. However, many African countries have failed to bring adequate solutions to their catastrophes. AIDS is the most striking example that gives room to such interpretation. Given the fact that there is still no cure for HIV/AIDS and no vaccine for the virus, it is all the more frightening to realize that nearly two-thirds of the world’s HIV-positive people live on our continent. The HIV/AIDS epidemic has actually had a tremendous impacton many parts of African society.